(untitled) (Update Dental College Journal, 2013)
Deep cervical fascia forms a connective tissue sheath around the thyroid gland. Delicate trabeculae and septa penetrate the gland indistinctly dividing the gland into lobes and lobules which in turn composed of follicles.1,2,3 These follicles are structural units of thyroid gland which varies greatly in size and shape.4 The number of follicles varies in different age groups. The study was carried out to see the percentage of area occupied by follicles in the stained section of thyroid glands in different age groups. The collected samples were grouped as A (3.5 20yrs), B (21- 40yrs) & C (41 78yrs). Percentage of area occupied by follicles was (58.55±10.72) in group A, (63.79±12.35) in group B + (63.39±8.29) in group C. DOI: http://dx.doi.org/10.3329/updcj.v1i2.13981 Update Dent. Coll. j. 2011: 1(2): 17-20